PENGUATAN IDENTITAS WARGA NEGARA MELALUI PENDIDIKAN BERBASIS KEARIFAN LOKAL DALAM KONTEKS PELESTARIAN DAS KALIGARANG - Yuliyani, Dwi Nur; Khoirunnisak, Anis (Journal of Democratia; Vol 4 No 2 (2025): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan Hukum, 2025)
The environmental crisis that occurred in the Kaligarang River Basin Area (DAS), Semarang City, shows the weak ecological awareness of residents caused by air pollution, sedimentation, and ongoing ecosystem damage. Social changes and urban development have caused local cultural values ??that will affect the environment to be marginalized. In fact, these values ??are important potentials in the formation of ecological identity. This study aims to explore the role of local cultural revitalization strategies in building the identity of citizens who care about the environment. A descriptive qualitative approach was used in this study, with data collection techniques through field observations, in-depth interviews with traditional leaders, teachers, and residents, as well as cultural documentation that is still carried out by the community around the Kaligarang DAS. The results of the study indicate that cultural practices such as nyadran kali, larung sesaji, and customary taboos in utilizing water resources contain environmental conservation principles that are relevant to the character of education and citizenship. These values ??can be revitalized through contextual learning based on integration between Geography and PPKn subjects. Revitalization of local culture not only reflects collective awareness and environmental ethics,but also becomes an effective means of instilling values ??of responsibility as citizens towards environmental sustainability. Therefore, local culture integrated into education can form a strong and sustainable ecological identity.